Embryo sac development in yellow passion fruit Passiflora edulis f. flavicarpa (Passifloraceae) - Margarete Magalhães de Souza; Telma Nair Santana Pereira; Magali Hoffmann; Edésio J.T. de Melo; Ricardo Pereira Louro (Genetics and Molecular Biology, 2002)
The yellow passion fruit, Passiflora edulis f. flavicarpa, is one of the most important Brazilian fruit crops. It is an allogamous, diploid, and self-incompatible species. It has hermaphrodite, solitary flowers, located in the leaf axils and protected by leaf bracts. The flower has an androgynophore, which is a straight stalk supporting its reproductive parts. There are usually five anthers, located at the tip of each of the five filaments. The ovary is borne just above the filaments, at the top of the androgynophore; there are three styles that are united at their base, and at the top there are three stigmas. The objective of this research was to observe embryo sac development in yellow passion flowers. Ovaries at different stages of development were fixed in FAA (formalin, acetic acid and alcohol solution), hydrated, stained with Mayer’s hemalum, and dehydrated. Ovules were cleared by using methyl salicylate, mounted on slides, and observed through a confocal scanning laser microscope. The yellow passion fruit ovule is bitegmic, crassinucellate, and anatropous, and its gametophyte development is of the Polygonum type. After meiosis, functional megaspores under go three successive mitotic divisions, resulting in an eight-nucleate megagametophyte: the egg apparatus at the micropylar end, two polar nuclei at the cell center, and three antipodals at the chalazal end. The egg apparatus is formed by an egg cell and two synergids, each with a filiform apparatus. The mature embryo sac has an egg cell, two synergids, two polar nuclei, and three antipodes, as has been described for most angiosperms.